TRANSFORMASI MINDSET WIRAUSAHA MELALUI BIMBINGAN KARIR ENTREPRENEUR BAGI PELAKU UMKM JEMBER - Azis, Akhmad Rifqi; Permatasari, Devi; Suharmawan, Wahid (STKIP PGRI SITUBONDO, 2025)
This community service program aims to transform the entrepreneurial mindset of micro-enterprises in Jember Regency through the Entrepreneurial Career Guidance approach. The background lies in the fact that many micro-entrepreneurs operate without planning, long-term vision, or growth motivation. The method involved counselling sessions, reflective discussions, career mapping, and evaluation through pre- and post-tests. The activity was conducted at CV. Serba Murah Mitra Sukses Jember with 30 micro-entrepreneurs participating. Results showed a 41.3% increase in participants’ understanding of the growth mindset concept, and 86.6% successfully developed a structured entrepreneurial career map. The program also fostered collaborative networking among participants who continued communication beyond the program. This approach proved effective in enhancing self-awareness, motivation, and strategic business planning skills. The model is recommended for replication in other community empowerment programs on a sustainable basis.